2017
DOI: 10.1177/0950422217715200
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing graduate prospects by recording and reflecting on part-time work

Abstract: Business leaders are becoming increasingly explicit regarding the skills, attributes and behaviours expected of graduate entrants. These skills are often developed through a combination of academic studies and work experience. While universities are increasingly providing opportunities for experiential learning, typically a placement year or internship, a growing number of students are undertaking self-initiated part-time work alongside their full-time degree studies. This part-time employment, typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Similarly, connecting theoretical frameworks with students’ own work experiences supports the recommendations of Major (2005), who feels that effective learning is best facilitated by presenting learners with an opportunity to become involved in the relationship between theory and practice, rather than seeing them as separate entities. Darolia (2014) and Evans and Richardson (2017) even recommend that students should be awarded academic credit for part-time work activities, and therefore that such activities should be more formally embedded in assessment regimes.…”
Section: Students’ Part-time Work Activitymentioning
confidence: 99%
“…Similarly, connecting theoretical frameworks with students’ own work experiences supports the recommendations of Major (2005), who feels that effective learning is best facilitated by presenting learners with an opportunity to become involved in the relationship between theory and practice, rather than seeing them as separate entities. Darolia (2014) and Evans and Richardson (2017) even recommend that students should be awarded academic credit for part-time work activities, and therefore that such activities should be more formally embedded in assessment regimes.…”
Section: Students’ Part-time Work Activitymentioning
confidence: 99%
“…The skills being developed in these part-time positions are therefore often those demanded by businesses for graduate jobs (CMI, 2014). As Davies (2000) and Evans and Richardson (2017) recognize, this yields an opportunity for universities not just to welcome and encourage but to embrace and integrate the part-time work activities of their students by accrediting the part-time work-based experience against degree learning outcomes, thereby reinforcing the employment credentials of their graduates.…”
Section: The Current Proposition: Accrediting University Students’ Pamentioning
confidence: 99%
“…In a recent viewpoint article, Evans and Richardson (2017) suggested that there was an opportunity for universities to accredit part-time work activities undertaken by students while studying for a degree. This suggestion was based on the premise that such part-time work provides skills, attitudes and behaviours demanded by employers.…”
mentioning
confidence: 99%
“…Islamic economics universities should think about their graduates' future by providing training and strategies for getting jobs. Off-the-job training, such as Islamic banking practices, and on-the-job training internships/work practices in the Islamic banking industry, are considered useful in helping students in Islamic economic colleges in the recruitment process (Evans and Richardson, 2017). In addition, Alhalwaki and Hamdan (2019) argue that the internationalization of higher education is a university strategy in responding to the pace of globalization.…”
Section: Introductionmentioning
confidence: 99%